Communicating today the essentials - Zeuschner, Raymond F. (Pearson Allyn and Bacon, 2003)
Communicating Today: The Essentials combines a solid grounding in theory and history with competency-oriented chapters on interviewing, group discussion, and public speaking. Through this text, students will gain an appreciation for the development of the field, its major areas of emphasis and its relevance and applications to contemporary issues. Each of the 15 chapters features five themes to augment the focus of the chapter: history, diversity, competencies, critical thinking, and technology. Communicating Today: The Essentials challenges students to think about issues, acquire skills and knowledge, understand concepts, and apply terms and theories to their entire communication repertoire.